'Specimens Distributed': The circulation of objects from Kew's Museum of Economic Botany, 1847–1914. (13th May 2019) - Cornish, Caroline; Driver, Felix
Abstract: This paper presents research on the dispersal of objects from the Museum of Economic Botany at the Royal Botanic Gardens, Kew (rbgk ) from 1847 to 1914. Established by William Hooker, the museum received thousands of objects from around the world, the display of which was designed to illustrate plants' properties and economic potential. The paper argues that the conventional focus in museum studies on processes of acquisition and accumulation captures only one side of collections' history. Drawing on research in archives and collections at Kew and elsewhere, we highlight the redistribution of specimens and artefacts from Kew's museum through a variety of channels. We focus on three modes of circulation: firstly, Kew's role as a clearing house for collections; secondly the exchange of objects; and thirdly the distribution of specimens and artefacts to schools across the British Isles, a practice which became prevalent towards the end of the period.